Studies Towards the Synthesis of Crotogoudin - Ushakov, Dmitry B.; Maier, Martin E. (Synlett, 2013)
An effective synthesis of the tricyclic core structure of the new diterpene crotogoudin was achieved. The synthesis features an intermolecular domino Michael reaction to construct a bicyclo[2.2.2]octane motif and an aldol condensation to close ring B. Stork reductive alkylation with allyl bromide proceeded from the β side, resulting in the wrong stereochemistry at C-10.
Keywords: crotogoudin; atisane; diterpene; domino Michael reaction; Stork reductive alkylation